A STUDY ON THE ETHICAL ASPECTS OF THE PUBLIC DISTRIBUTION SYSTEM: WITH REFERENCE TO JAMIRAH GAON PANCHAYAT SAMABAY SAMITI OF DIBRUGARH DISTRICT - Sarmah, Ananya; Gogoi, Himadree (International Journal of Research -GRANTHAALAYAH, 2017)
Public Distribution System (PDS), an Indian food security system, is a means for ensuring food security to the poor and the needy. Essential commodities like rice, flour, kerosene etc., are supplied to the people under the PDS at subsidised prices. It was started with the objective to maintain price stability of essential commodities, providing access to food and other essential items at affordable prices to the population. It is important for the functioning of the PDS to be ethical in order to meet the true objectives with which this system was actually started. It has been seen that there have been a number of malpractices in the functioning of the system. This paper looks into the ethical aspects of the functioning of PDS. In doing so, customers’ point of view in respect of the overall system has been taken. And an effort has been made to bring to light any malpractice that may be occurring in the system. This paper is a descriptive one which takes a sample of 46 respondents that have been selected on the basis of the number of fair price shops in the JamirahGaon Panchayat SamabaySamiti of Dibrugarh district of Assam.